Jesus Driven Ministry - Fernando, Ajith (Secunderabad OM Books, 2004)
In this book, Ajith Fernando identifies the foundational elements that allow you to be both effective and joyful in your service. He shows from Jesus' own ministry that relating to the people you minister to, retreating from busyness to prayer, being affirmed and empowered by God, discipling younger leaders, and gaining strength from God's Word must be at the heart of your ministry. Rich in Scripture and full of stories from Fernando's own years of ministry, this book will challenge you and provide resources to help you cultivate a long and fruitful life of ministry.
Keywords: Pastoral theology. RELIGION / Christian Ministry / Pastoral Resources